Rictor is a central target of the molecular network of cardiac ProtectomiRs. (10th June 2022) - Makkos, A; Agg, B; Varga, ZV; Giricz, Z; Gyongyosi, M; Lukovic, D; Schulz, R; Bartekova, M; Gorbe, A; Ferdinandy, P
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Research, Development and Innovation Office of Hungary (NKFIA; NVKP-16-1-2016-0017 National Heart Program and OTKA-FK 134751); MTA-SE System Pharmacology Research Group, Department of Pharmacology and Pharmacotherapy, Semmelweis University, H-1089 Budapest, Hungary We have previously identified several cardiac microRNAs that are involved in cardioprotection and termed them as ProtectomiRs. mRNA targets of these ProtectomiRs may reveal new drug targets for cardioprotection. Here we aimed to identify key molecular targets of ProtectomiRs and confirm their association with cardioprotection in a translational pig model of acute myocardial infarction. Network theoretical approach was utilized to identify 882 potential target genes of 18 previously described protectomiRs. Rictor gene was the most central and it was ranked first in the protectomiR-target mRNA molecular network with the highest node degree of 5. Therefore, expression of Rictor and its targeting microRNAs were further validated in heart samples obtained from a translational pig model of acute myocardial infarction and cardioprotection induced by pre- or postconditioning. Three out of five Rictor-targeting pig homologue of rat ProtectomiRs showed significant upregulation in postconditioned but not in preconditioned pig hearts. Rictor was downregulated at the mRNA and protein level in ischemic postconditioning but not in ischemic preconditioning. This is the first demonstration that Rictor is the central molecular target of ProtectomiRs and that decreased Rictor expression may regulate ischemic postconditioning-, but not preconditioning-induced acute cardioprotection. We conclude that Rictor is a potential novel drug target for acute cardioprotection.